Decontamination methods to restore the biocompatibility of contaminated titanium surfaces - Jin, Seong-Ho (J Periodontal Implant Sci, 2019)
PURPOSE: The reaction of cells to a titanium implant depends on the surface characteristics of the implant which are affected by decontamination. The aim of this study was to evaluate the cytocompatibility of titanium disks treated with various decontamination methods, using salivary bacterial contamination with dental pellicle formation as an in vitro model. METHODS: Sand-blasted and acid-etched (SA) titanium disks were used. Three control groups (pristine SA disks [SA group]; salivary pellicle-coated SA disks [pellicle group]; and biofilm-coated, untreated SA disks [NT group]) were not subjected to any decontamination treatments. Decontamination of the biofilm-coated disks was performed by 14 methods, including ultrasonic instruments, rotating instruments, an air-powder abrasive system, a laser, and chemical agents. MG63 cells were cultured in the presence of the treated disks. Cell proliferation assays were performed on days 2 and 5 of cell culture, and cell morphology was analyzed by immunofluorescence and scanning electron microscopy (SEM). A vascular endothelial growth factor (VEGF) assay was performed on day 5 of culture. RESULTS: The cell proliferation assay revealed that all decontaminated disks, except for the 2 groups treated using a plastic tip, showed significantly less cell proliferation than the SA group. The immunofluorescence and SEM analyses revealed that most groups showed comparable cell density, with the exception of the NT group, in which the cell density was lower and bacterial residue was observed. Furthermore, the cells grown with tetracycline-treated titanium disks showed significantly lower VEGF production than those in the SA group. CONCLUSIONS: None of the decontamination methods resulted in cytocompatibility similar to that of pristine SA titanium. However, many methods caused improvement in the biocompatibility of the titanium disks in comparison with the biofilm-coated, untreated titanium disks. This suggests that decontamination is indispensable for the treatment of peri-implantitis, even if the original biocompatibility cannot be restored.